MODERN TRENDS AND DEVELOPMENT FACTORS OF THE IMPLEMENTATION OF DIGITAL TECHNOLOGIES IN THE EDUCATION SYSTEM - Feruz Sanakulovich Aktamov (Modern American Journals, 2025)
This article discusses digital technologies, cloud technologies, the use of digital technologies in education, digital technologies in the education system, advantages and disadvantages of using digital technologies.
Keywords: Digital technologies, digital technologies in education, cloud technologies.